2016
DOI: 10.1089/bio.2015.0108
|View full text |Cite
|
Sign up to set email alerts
|

A Biospecimen Proficiency Testing Program for Biobank Accreditation: Four Years of Experience

Abstract: Biobanks produce and distribute biospecimens, ensuring their fitness for purpose and accurately qualifying them before distribution. In their efforts toward professionalization, biobanks can nowadays seek certification or accreditation. One of the requirements of these standards is regular participation in Proficiency Testing (PT) programs. An international PT program has been developed and provided to biobanks and other laboratories that perform specific tests to qualify different types of biospecimens. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
(34 reference statements)
1
10
0
2
Order By: Relevance
“…Since 2015, we have been participating annually in the IBBL-PT (Gaignaux et al 2016), which is endorsed by the International Society for Biological and Environmental Repositories (ISBER). We participated in the tests for PBMC isolation, cell viability and DNA quantification.…”
Section: Standardization Of Biobank Quality Controlmentioning
confidence: 99%
“…Since 2015, we have been participating annually in the IBBL-PT (Gaignaux et al 2016), which is endorsed by the International Society for Biological and Environmental Repositories (ISBER). We participated in the tests for PBMC isolation, cell viability and DNA quantification.…”
Section: Standardization Of Biobank Quality Controlmentioning
confidence: 99%
“…Second and more importantly, the measurement kit used by Lee et al was the Milliplex Map Human Cytokine/ Chemokine Magnetic Bead Panel kit-Immunology Milliplex Assay (Millipore), which is different from the kit we used (R&D Systems). These differences underline the critical importance of using common reference (QC) materials for cytokine measurements, as it was recommended by Aziz et al [21] and/or participating in international ring trials [27]. Interestingly, the MSD and R&D kits used in our study, showed similar concentration results for IL16 in EDTA plasma, but the R&D kit showed 3-5 times higher concentration results for IL8 in serum and in citrate plasma than the MSD kit, using the same samples from three IBBL donors.…”
Section: Discussionmentioning
confidence: 99%
“…The quality management of the preanalytical phase in biobanks includes some new concepts such as the validation of each processing method for reproducibility, robustness, fitness-for-purpose and stability of output specimens [37]. The development and implementation of "in-process quality control materials" is part of the continuous quality assurance, as well as participation in EQA "processing schemes" [38]. The purpose of most of the samples produced by biobanks is not their use in clinical diagnostics, but rather in research projects.…”
Section: Managing Preanalytical Variables In Bio-bankingmentioning
confidence: 99%